Analysis Time Series (ARIMA): To determine the Development of Oil Exports in Indonesia - Muthahharah, Isma; Meliyana, Sitti Masyitah (University of Mataram, 2025)
Oil exports are the largest export in Indonesia. Indonesia's oil exports from year to year tend to fluctuate and in the end continue to decline, however in the last three years exports of oil products have continued to increase from the previous year. This research aims to analyze the development of oil exports in Indonesia. The data used in this research is doil export data from 1996 to 2023 obtained from data Indonesian Central Statistics Agency (BPS). The method used to analyze development of oil exports in Indonesia is Autoregressive Integrated Moving Average (ARIMA). The research results show that Indonesia's oil exports have experienced significant fluctuations from year to year, with a quite striking decline in export volume in recent years. The ARIMA model (2,2,2) was identified as the best model for predicting future behavior from oil export data. This model succeeds in describing the intrinsic patterns in the export data well. Using the ARIMA (2,2,2) model it is known that forecasting results development of oil exports in Indonesia (2024-2035) will experience an increase from the previous year.